2014
DOI: 10.1111/asj.12307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrate addition to a diet on fermentation and microbial populations in the rumen of goats, with special reference to Selenomonas ruminantium having the ability to reduce nitrate and nitrite

Abstract: This study investigated the effects of dietary nitrate addition on ruminal fermentation characteristics and microbial populations in goats. The involvement of Selenomonas ruminantium in nitrate and nitrite reduction in the rumen was also examined. As the result of nitrate feeding, the total concentration of ruminal volatile fatty acids decreased, whereas the acetate : propionate ratio and the concentrations of ammonia and lactate increased. Populations of methanogens, protozoa and fungi, as estimated by real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 38 publications
(146 reference statements)
6
49
2
1
Order By: Relevance
“…At the low concentrations of 3-NOP and of nitrite required to completely inhibit methanogenesis, these compounds are not toxic to animals (19,35,36). 1,3-Propanediol (37) and nitrite (38) are commonly occurring intermediates in the rumen.…”
Section: Resultsmentioning
confidence: 99%
“…At the low concentrations of 3-NOP and of nitrite required to completely inhibit methanogenesis, these compounds are not toxic to animals (19,35,36). 1,3-Propanediol (37) and nitrite (38) are commonly occurring intermediates in the rumen.…”
Section: Resultsmentioning
confidence: 99%
“…Effects of nitrate on ruminal protozoa are contrasting. Asanuma et al (2015) reported 86% reduction in protozoa abundance in goats receiving potassium nitrate, but their numbers were not affected in lambs (van Zijderveld et al, 2010) or cows (Guyader et al, 2015a). Similarly contrasting results were reported with the addition of linseed oil, some authors observing a linear reduction in protozoa numbers with increasing amounts of linseed (Martin et al, 2016), whereas others report no change even with high amounts of added fatty acids (Benchaar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Polyunsaturated fatty acids are known to have a toxic effect on some ruminal bacteria, especially cellulolytic ones (Maia et al, 2007), however, we did not observe a reduction in the numbers of the three main cellulolytic bacteria ( Fibrobacter succinogenes, Ruminococcus albus, Ruminococcus flavefaciens ). In vitro , nitrate inhibited growth of the same three species; in vivo their numbers were reduced in the rumen of goats (Asanuma et al, 2015), but increased in steers (Zhao et al, 2015) fed nitrates. Ruminococcus species adapt to nitrates, whereas methanogens and F. succinogenes do not (Zhou et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the rumen, NIT decreases methanogenesis by competing for [2H] during dissimilatory nitrate reduction to ammonium (NH4+; DNRA) or during denitrification leading to nitrous oxide (N 2 O) production (Yang et al, 2016). At the same time, nitrite produced as an intermediary product of DNRA would have a direct toxic effect toward methanogenic Archaea (Klüber and Conrad, 1998; Asanuma et al, 2015). Nitrate decreased CH 4 production in lactating dairy cows (21 g nitrate/kg dry matter [DM], −23.4% CH 4 ; Olijhoek et al, 2016), steers (30 g nitrate/kg DM, −29.4% CH 4 ; Newbold et al, 2014) and sheep (20 g nitrate/kg DM, −16.5% CH 4 ; de Raphélis-Soissan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%